Collagen XIX is required for pheromone recognition and glutamatergic synapse formation in mouse accessory olfactory bulb - Amos, Chase; Fox, Michael A.; Su, Jianmin (Frontiers in Cellular Neuroscience, 2023)
Abstract In mammals, the accessory olfactory bulb (AOB) receives input from vomeronasal sensory neurons (VSN) which detect pheromones, chemical cues released by animals to regulate the physiology or behaviors of other animals of the same species. Cytoarchitecturally, cells within the AOB are segregated into a glomerular layer (GL), mitral cell layer (MCL), and granule cell layer (GCL). While the cells and circuitry of these layers has been well studied, the molecular mechanism underlying the assembly of such circuitry in the mouse AOB remains unclear. With the goal of identifying synaptogenic mechanisms in AOB, our attention was drawn to Collagen XIX, a nonfibrillar collagen generated by neurons in the mammalian telencephalon that has previously been shown to regulate the assembly of synapses. Here, we used both a targeted mouse mutant that lacks Collagen XIX globally and a conditional allele allowing for cell-specific deletion of this collagen to test if the loss of Collagen XIX causes impaired synaptogenesis in the mouse AOB. These analyses not only revealed defects in excitatory synapse distribution in these Collagen XIX-deficient mutants, but also showed that these mutant mice exhibit altered behavioral responses to pheromones. Although this collagen has been demonstrated to play synaptogenic roles in the telencephalon, those roles are at perisomatic inhibitory synapses, results here are the first to demonstrate the function of this unconventional collagen in glutamatergic synapse formation.